2003
DOI: 10.1159/000069307
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively Irradiated Rectal Carcinoma: Analysis of the Histopathologic Response and Predictive Value of Proliferating Cell Nuclear Antigen Immunostaining

Abstract: Objectives: To investigate the relationship between the histopathologic effects of preoperative chemoradiotherapy in rectal cancer and the proteins, proliferating cell nuclear antigen (PCNA) and p53. Methods: Samples from 73 tumors were examined. The histopathologic effects observed in the resected specimens induced by preoperative chemoradiotherapy were correlated with the inmunohistochemical expression of PCNA and p53 in biopsies obtained by rectoscopy before chemoradiotherapy. Results: Thirty-five tumors sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…High proliferative activity determined by proliferating cell nuclear antigen immunostaining and Ki-67 labeling were predictive of the response to preoperative CRT in patients with rectal canecr. 32,33 This study also suggested that neoadjuvant CRT induced COX-2 expression to COX-2-negative rectal cancer. The COX-2-positive rate in patients with rectal cancer was significantly increased after CRT.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…High proliferative activity determined by proliferating cell nuclear antigen immunostaining and Ki-67 labeling were predictive of the response to preoperative CRT in patients with rectal canecr. 32,33 This study also suggested that neoadjuvant CRT induced COX-2 expression to COX-2-negative rectal cancer. The COX-2-positive rate in patients with rectal cancer was significantly increased after CRT.…”
Section: Discussionmentioning
confidence: 61%
“…2). 32,33 When there was a discrepancy in scoring between two investigators, consensus was achieved after discussion.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of p21 screening is warranted, as the referenced studies in (Salonga, Danenberg et al 2000), (Lenz, Danenberg et al 1998). Numerous studies assessing TS expression have found that pretreatment biopsies negative for TS were predictive of response (Saw, Morgan et al 2003), (Diez, Ramos et al 2003), (Jakob, Liersch et al 2008), (Negri, Campanini et al 2008). 3 studies revealed a better outcome with low or absent pretreatment TYMS expression, however another study demonstrated better outcome with high TYMS expression.…”
Section: P21mentioning
confidence: 99%
“…Ряд исследований выявил зависи-мость между хорошим ответом опухоли на неоадъювантную терапию и низкой экспрессией тимидилатсинтетазы (или во-обще её отсутствием), однако другие ра-боты свидетельствуют об обратной связи: между значительной регрессией опухоли и высокой экспрессией тимидилатсинтетазы [5][6][7][8]. Однако работы, определившие корре-ляцию между регрессией опухоли в ответ на неоадъювантную радиохимиотерапию и высокой экспрессией тимидилатсинтетазы, на проводимую химиолучевую терапию (с преобладанием больных с низкой экспрессией) и полной регрессией опухоли (с преобладанием больных с высокой экспрессией).…”
unclassified